Predicting self-determined motivation of elite female Volleyball players from leadership styles of coaches in Iran - Zardoshtian, S.; Naghshbandi, S.; Jabari, N. (International Journal of Sports Science and Engineering, 2011)
The purpose of this study was to predict self-determined motivation of elite female volleyball players from leadership styles of coaches. The sample composed of 12 volleyball teams in woman league (137 athletes) in Iran. Leadership styles were measured by Leadership Scale for Sports (LSS) (Chelladurai & Saleh, 1980) and self-determined motivation was measured by Sport Motivation Scale (SMS) (Pelletier et al., 1995). The statistical procedure also was based on descriptive statistics and inferential statistics including multivariable regression. The results indicated that democratic behavior and autocratic behavior were related to self-determined motivation (intrinsic motivation, extrinsic motivation, and amotivation). Moreover, training and instruction was related to two dimensions of self-determined motivation (intrinsic motivation, extrinsic motivation). Social support was associated only with one dimension of self-determined motivation (amotivation). However, positive feedback had no relationship with self-determined motivation. It is suggested that coach regards his leadership style to increase self-determined motivation of athletes.